Analysis of Trading Volume Activity Before And After The Announcement Of Covid-19 at PT Indosat - Adityo Leonardo Rahayaan; Ngurah Pandji Mertha Agung Durya (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
This study aims to determine the effect of stock trading volume due to the impact before and after the Covid-19 event through an official announcement by the president. The population and sample in this study were the company PT Indosat Tbk. This study uses purposive sampling. The data source used is secondary data. Based on the analysis of the paired sample T-test using the SPSS 24.0 program, it was found that stock trading volume had a significant effect before and before the announcement